CXCL1-Triggered Interaction of LFA1 and ICAM1 Control Glucose-Induced Leukocyte Recruitment during Inflammation In Vivo - Kirsten Buschmann; Lutz Koch; Natascha Braach; Hanna Mueller; David Frommhold; Johannes Poeschl; Peter Ruef (Mediators of Inflammation)
It is well acknowledged that proinflammatory stimulation during acute hyperglycemia is able to aggravate inflammatory diseases. However, the mechanisms of proinflammatory effects of glucose are controversially discussed. We investigated leukocyte recruitment after intravenous injection of glucose in different inflammatory models using intravital microscopy. Flow chamber experiments, expression analysis, functional depletion, and knockout of key adhesion molecules gave mechanistic insight in involved pathways. We demonstrated that a single injection of glucose rapidly increased blood glucose levels in a dose-dependent manner. Notably, during tumor necrosis factor (TNF) α-induced inflammation leukocyte recruitment was not further enhanced by glucose administration, whereas glucose injection profoundly augmented leukocyte adhesion and transmigration into inflamed tissue in the trauma model, indicating that proinflammatory properties of glucose are stimulus dependent. Experiments with functional or genetic inhibition of the chemokine receptor CXCR2, intercellular adhesion molecule 1 (ICAM1), and lymphocyte function antigen 1 (LFA1) suggest that keratino-derived-chemokine CXCL1-triggered interactions of ICAM1 and LFA1 are crucially involved in the trauma model of inflammation. The lacking effect of glucose on β2 integrin expression and on leukocyte adhesion in dynamic flow chamber experiments argues against leukocyte-driven underlying mechanisms and favours an endothelial pathway since endothelial ICAM1 expression was significantly upregulated in response to glucose.